Analisa Kompetensi dalam Meningkatan Kepuasan Kerja dan Kinerja Karyawan - Zulkifli Rusby; Astri Ayu Purwati; Muhammad Arif; Zulfadli Hamzah (COSTING : Journal of Economic, Business and Accounting, 2020)
The lack of competency possessed by BMT employees in Pekanbaru City both related to the competence of sharia science and from business development competencies, lack of employee ability to manage or organize Islamic financial service cooperatives and the low level of job satisfaction possessed by BMT employees . This research method is a descriptive method with a quantitative approach. Data analysis technique used in this research is quantitative analysis using SEM (Structural Equation Modeling) model with PLS program. The population in this study were all BMT employees in the city of Pekanbaru. The number of samples in this study were 79 respondents. The results of this study indicate there is a direct influence between competencies on Job Satisfaction of BMT employees in Pekanbaru, there is a direct effect between satisfaction on the performance of BMT employees in Pekanbaru, there is no indirect effect between competencies on performance through job satisfaction of BMT employees in Pekanbaru. Through the results of this study it is expected that all BMTs in Pekanbaru to pay attention and be more focused on aspects of employee job satisfaction because the level of employee job satisfaction is very significant influence on the performance of BMT employees in Pekanbaru. Keywords: Competence, Job Satisfaction and Employee Performance.